Study of Technical Qualification Evaluation for Construction Work Tender on Under Bid Price Contract - Adel Emir Fuadi Harahap; Benny Hidayat; Akhmad Suraji (CIVED, 2025)
Based on data from LPSE Padang City for the 2021 and 2022 fiscal years, it was found that one third of the work packages in those fiscal year had an Under Bid Price Contract (UBPC) or an offer with less than 80% of the Owner’s Estimate (OE). The purpose of this study is to examine the conformity between field implementation and technical qualification documents in construction work tenders with less than 80% OE or under bid price contracts in Padang City and its impact on small qualifications. Qualitative analysis based on the results of interviews with implementing contractors from several institutions or agencies involved in the procurement process of goods/services in Padang City was used in this study. This study only focuses on the technical qualifications of construction work tenders on under bid price contracts in Padang City using the tender method and the one-envelope method with a small category Construction Services Business License for the 2023 Fiscal Year. The results of the study show that qualification documents and contract documents with HPS of less than 80% in the implementation in the field are still appropriate. The results of interviews with seven contractors showed that the main equipment and managerial personnel used were also still appropriate. The profit target has been achieved by 4 out of 7 respondents (57.14%) and the remaining 3 out of 7 respondents did not get any profit, this is known from the end of the contract period. 3 out of 7 respondents (42.86%) have minor disabilities and 4 out of 7 respondents do not have minor disabilities. 7 respondents (100%) also did not experience delays in work. 3 out of 7 respondents experienced one contract addendum and the remaining 4 out of 7 experienced two contract addendums.